Monitoring of the technical condition of buildings and structures under operational conditions - Umanets, I.; Basarab , V. (Ways to Improve Construction Efficiency, 2023)
The article is devoted to monitoring the technical condition of buildings and structures in operational conditions. Monitoring the technical condition of buildings and structures helps to understand the real condition and get recommendations for eliminating defects. Assessment of the technical condition of buildings and structures is necessary to ensure their operational suitability. Usually, monitoring includes a number of different methods that allow to assess the technical condition of the object in dynamics based on periodic (monthly, weekly) observations. The relevance of research was emphasized, which was determined by the practical need to assess the technical condition of the load-bearing structures of buildings and structures under the influence of natural and climatic factors and human activity, which would allow predicting the occurrence and development of emergency situations with high reliability. The purpose of the work is established, which consists in the development of a theoretical-experimental methodology for assessing the technical condition of load-bearing structures of buildings and structures during monitoring using modern information technologies for data acquisition and processing. An analysis of modern natural (experimental) methods of assessing the technical condition of buildings and structures, as well as computer modeling methods, was carried out. The expediency of conducting the survey, which consists in establishing the real bearing capacity and operational suitability of the building (structure), is indicated. The purpose of the survey is to obtain data to determine the reliability of the building, the need for strengthening, repair, reconstruction, modernization and development of the necessary project documentation. The principles of building a system for monitoring the technical condition of buildings (buildings), the basic structure, and engineering solutions were described. An analysis of the main theoretical methods of modeling the technical condition of the building was carried out. The method of building an information system for obtaining data from sensors of physical parameters, as well as recording, processing, comparing with theoretical models and making management decisions in case of deviation of operational parameters from permissible values was given. It is proposed to solve the inverse problem using predictive mathematical models, namely: designing a building (structure) with predetermined (according to the project) parameters of technical condition and operational reliability.